2001
DOI: 10.1292/jvms.63.1003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maturational Age of Porcine Oocytes on the Induction of Activation and Development In Vitro Following Somatic Cell Nuclear Transfer.

Abstract: ABSTRACT. To determine the effect of maturational age of porcine oocytes on the induction of activation and development following nuclear transfer, we investigated maturation rate and efficacy of oocyte activation treatment with an electrical stimulus (ES) and cycloheximide (CHX) at various timing of maturation culture. Most oocytes developed to the metaphase II (MII) stage after 32 hr of maturation culture. Both in newly matured (32 and 36 hr of age) and MII-arrested (42 and 48 hr of age) oocytes, ES followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 33 publications
1
29
3
Order By: Relevance
“…MPF activity in cytoplasts plays a key role(s) for development of NT embryos, since the length of the maturation period affects the ability of porcine cytoplasts to support the development of NT embryos (Cheong et al 2000, Ikeda & Takahashi 2001, Miyoshi et al 2002. In this study, we found that high MPF activity elevated in cytoplasts improved the development of NT embryos.…”
Section: Mpf Activity In Porcine Nt Embryossupporting
confidence: 54%
See 2 more Smart Citations
“…MPF activity in cytoplasts plays a key role(s) for development of NT embryos, since the length of the maturation period affects the ability of porcine cytoplasts to support the development of NT embryos (Cheong et al 2000, Ikeda & Takahashi 2001, Miyoshi et al 2002. In this study, we found that high MPF activity elevated in cytoplasts improved the development of NT embryos.…”
Section: Mpf Activity In Porcine Nt Embryossupporting
confidence: 54%
“…When the donor nuclei in G0/G1 of the cell cycle are transferred into recipient cytoplasts with a high level of maturation promoting factor (MPF) before activation, they are transformed to nuclear envelope breakdown (NEBD) and then premature chromosome condensation (PCC) (Ikeda & Takahashi 2001). In the mouse and bovine, this PCC of the transferred nucleus was related to the success of cloning (Shin et al 2002, Wakayama et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maturational age of porcine oocytes affects the potential of subsequent embryo development. In pigs, newly matured oocytes showed lower developmental competence after IVF [34] or parthenogenetic activation [35] compared with oocytes cultured for an additional 8-10 h. This might be due to inadequate cytoplasmic maturation and/or immaturity of the metaphase spindle of MII stage oocytes immediately after MIIarrest [36]. The time at which the oocytes reached the MII stage in mNCSU37+PVA was delayed compared with the other maturation media (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…In both species, when a donor nucleus in the G0/G1 stage of the cell cycle is transferred to an enucleated oocyte, the PCC of the transferred nucleus is related to the success of cloning and probably reprogramming [12]. Donor nuclei in the G0/G1 stage show nuclear envelope breakdown (NEBD) and PCC when they are transferred into recipient cytoplasts with high levels of maturation/ metaphase promoting factor (MPF) [19] before activation [20]. Methods that induce PCC in SCNT oocytes result in increased developmental potential, indicating that these processes may promote reprogramming of gene expression in the donor nucleus [12,[21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%